Human faces capture attention and attract first saccades without longer fixation. Issue 2 (7th February 2019) - Morrisey, Marcus N.; Hofrichter, Ruth; Rutherford, M. D.
ABSTRACT: Human faces attract attention, evidenced by reaction time (RT) advantages over non-face stimuli in visual search tasks. In the current study, participants' eye movements were tracked during a search task to test how the attentional capture of faces is related to looking behaviour. On each trial, participants were cued with a category name (automobiles, birds, chairs, dogs, faces, bodies, or plants). An array of images, one exemplar from each category, was then presented until participants indicated whether the target matched the cue. Results showed that faces as targets resulted in faster search times and were more likely to capture first fixations. Fixations on faces were also shorter compared to other categories. Faces captured attention, attracting first fixations, and participants appeared to be more fluent at processing faces, resulting in shorter fixations. Reaction time advantages for faces could be due to both attention capture and ultra-rapid processing.